SWOT analysis of Janani Suraksha Yojana among women of Western Uttar Pradesh, India - Shalki Mattas; Bhawna Pant; Saurabh Sharma; Priyanka Dobhal (Journal of Family Medicine and Primary Care)
Introduction: In April 2005, under the umbrella of National Rural Health Mission (NRM) in response to the slow and varied progress in improvement of maternal and neonatal health, the Government of India launched a scheme known as Janani Suraksha Yojana (ISY) Objectives: With the help of this study, we intend to understand the knowledge, source of information, awareness, and barriers to acceptance of JSY among women in Western Uttar Pradesh and conduct a SWOT analysis for the same. Material and Methods: The sample size was 300 and calculated using the prevalence of institutional delivery taken from National Family Health 2015-16 Survey (NFHS-4) in Uttar Pradesh, India, which was 67.8%. Data were analysed using appropriate statistical tests by Statistical Package for Social Sciences (SPSS) software and Microsoft excel. Results: Grassroot-level workers, namely, ASHA, ANM, AWW, and Dai, were an important source of information regarding JSY in the rural area with 68% beneficiaries saying that they got their information about JSY from them compared to only 22% in the urban area. Out of the 105 beneficiaries who delivered at home, the two most common reasons for noninstitutional delivery were the cost of the institutional delivery (51.4%) and home is convenient (47.696). Conclusion: Cash incentives help in the use of health services such as antenatal care, postnatal care, and counselling services. Less focus and ASHA coverage in urban areas as compared to rural areas.